Acquisitions in a Patent Contest Model with Large and Small Firms - Robin Kleer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2008)
Big companies and small innovation factories possess different advantages in a patent contest. While large firms typically have a better access to product markets, small firms often have a superior R&D efficiency. In this paper I model a patent contest with asymmetric firms. In a pre-contest acquisition game large firms bid sequentially for small firms to combine respective advantages. Sequential bidding allows the first large firm to wait strategically and let the other firm acquire. For low efficiencies this leads to an asymmetric market structure even though the initial situation is symmetric. Furthermore, acquisitions increase the chances for a successful innovation.
Keywords: O31; L24; G34; 330; patent contest; sequential acquisitions